Anxiety in mothers of infants newly diagnosed with cow’s milk protein allergy: A cross-sectional study - Sevinc, Nergiz; Korkut, Burcu; Sevinc, Eylem (Progress in Nutrition, 2021)
Introduction and Objectives: Anxiety symptoms are common in mothers of food-allergic children. Although cow's milk protein allergy (CMPA) is the most common food allergy in infants, little is known about whether CMPA has a known effect on anxiety in mothers. The first aim was to assess the anxiety levels in mothers of infants newly diagnosed with CMPA and compare to controls. The second aim was to determine whether there is a difference in anxiety levels of mothers by the symptoms of infants with CMPA. Material and methods: Mothers of seventy-three infants newly diagnosed with CMPA and 78 mothers of healthy infants were enrolled in this study. The CMPA group were divided into 5 subgroups according to symptoms of infants. The anxiety scores of the mothers were measured with State-Trait Anxiety Inventory (STAI). Results: The median score of the STAI-State (46 vs. 24) and the median score of the STAI-Trait (47 vs. 24) were significantly higher in CMPA group than the control group (p